How to deliver integrated care : a guidebook for managers - Kaehne, Axel, 1971-; Nies, Henk (Bingley, U.K. : Emerald Publishing Limited, 2021)
Care integration has become an important part of managing health and social care services all over the world. Bringing organisations together is thought to produce better access to care, reduce health care expenditure and improve quality of care for patients and service users. This book helps managers to think about how to collaborate in integrated care programmes. It provides practical advice on how to implement various aspects of care integration, such as fice, digital technology and evaluation. The book also contains chapters on the social and behavioural strategies, values and leadership approaches that should underpin integration. Each chapter contains key information based on the current state of research, illustrations from practical contexts and further reading.
Chapter 1. Integrated care - an introduction / Axel Kaehne, and Henk Nies -- Chapter 2. Ficing care integration / Eric van der Hijden, and Jeroen van der Wolk -- Chapter 3. Leadership in integrated care / Helen Dickinson, and Catherine Smith -- Chapter 4. Engaging patients for integrating care / Rachael Smithson, Christina Wicker, and Kimberley Pierce -- Chapter 5. Social dimensions of care integration / Karin Kee, Henk Nies, Marieke van Wieringen, and Bianca Beersma -- Chapter 6. Values in integrated care / Nick Zonneveld, Henk Nies, Elize van Wijk, and Mirella Minkman -- Chapter 7. Digital health enabling integrated care / Carolyn Steele Gray, Dominique Gagnon, and Nick Guldemond, Tim Kenealy -- Chapter 8. Implementing integrated care / Axel Kaehne -- Chapter 9. Evaluating integrated care / Walter Wodchis, Carolyn Steele Gray, Jay Shaw, Kerry Kuluski, Gayathri Embuldeniya, G Ross Baker, and Maritt Kirst.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Health services administration; Medical -- Administration; Medical administration & management